The Status of Ageism in Caring for Elderly Patients From Nurses' Perspective - Mohammad Ali Hosseini; Saeid Mehri; Masoud Fallahi-Khoshknab; Farahnaz Mohammadi-Shahbelaghi; Saeed Akbari-Zardkhaneh (Iran University of Medical Sciences, 2020)
Background: As the number of elderly people referred to hospitals increases, so does the number of discrimination reports in the care of the elderly, compared with younger people. This study aimed to investigate the status of ageism in caring for elderly patients from nurses' perspective. Methods: It was a descriptive cross-sectional study that was conducted in three selected hospitals of Ardabil province, Iran, in 2019. A total of 482 nurses were recruited by convenience sampling. The data were collected using a demographics questionnaire and the Ageism Scale in Hospital Care and analyzed using descriptive (frequency, percentage, mean, and standard deviation) and inferential statistics (the Pearson correlation coefficient, independent t-test, one-way ANOVA, and Scheffe post hoc test) in SPSS V. 20. Results: The mean age of the participants was 33 years. Most nurses showed moderate ageism when providing care to older adults. The level of ageism was significantly associated with age (P=0.002), gender (P=0.001), work experience (P=0.032), and the ward in which the nurses worked (P=0.001) Conclusion: The findings revealed that the study hospitals suffered ageism. Also, the level of ageism was associated with the age, gender, admission ward, and work experience of the nurses. Thus, it is suggested to consider appropriate interventions to prevent ageism, when designing and planning care for older adults.